New insights into the immediate outcome of collagenase injections for Dupuytren's contracture. (July 2016) - Warwick, D. J.; Graham, D.; Worsley, P.
Collagenase clostridium histolyticum is now established as an effective and safe option to treat patients with a single joint affected with Dupuytren's contracture. We have extended its use to natatory and combined cords. In a prospective consecutive series of 298 cords in 237 patients, the mean total extension loss improved in cords crossing the metacarpophalangeal joint from 46° to 1°, in cords crossing the proximal interphalangeal joint from 56° to 7°, in natatory cords from 130° to 25° and in combined cords from 102° to 16°. The immediate correction of combined cords and natatory cords was less reliable than that obtained in cords crossing the metacarpophalangeal joint or proximal interphalangeal joint. Less severe pre-intervention contractures tended to correct better. We found a high complication rate, which may cause alarm. A total of 21% developed skin splits, with the risk of skin splits generally increasing with more severe pre-injection deformity. Blood blisters were only encountered after manipulation of the more severe contractures. A total of 23 patients (8%) had a spontaneous rupture and 57 patients (19%) had a partial spontaneous rupture. Only 4.9% needed a second injection. We noticed a learning curve, with seven of the first 20 cords (35%) needing a second injection to achieve a satisfactory correction and then only seven (2.5%) in the rest. Level of evidence: IV